Efficacy of co-inoculation of the rhizobium and pseudomonas in combination with chemical fertilizer on the productivity of rice under legume-based cropping system - Kandel, Saraswoti; Pokhrel, Anil; Sharma, Reena; Rayamajhi, Kamana; Chaudhary, Suraj (Journal of Agriculture and Natural Resources, 2022)
The main production restriction in Nepal is a shortage of nitrogen and phosphorus-based fertilizers. In addition, the excessive use of chemical fertilizers to increase rice production alters the soils’ physicochemical and biological qualities. The effective application of biofertilizers obtained from beneficial microorganisms is on demand for increasing agriculture production as well as maintaining soil health sustainably. The experiment was conducted in a completely randomized block design (RCBD) with five treatments and four replications at Grain Legumes Research Program (GLRP), Khajura, Banke in order to find out the response of co-inoculation of Rhizobium and Pseudomonas in combination with different dose of recommended chemical fertilizers. The application of the co-inoculated Rhizobium and Pseudomonas at the dose of 800 g/ha along with the recommended N:P2O5:K2O dose of 100:60:30 kg/ha was found to be best effective among all treatment combinations. The maximum panicle length, biological yield, grain yield and thousand grains weight were 27.75 cm, 6.55 t/ha, 6.083 t/ha, and 27.67 g, respectively. In this study, co-inoculation of Rhizobium, Pseudomonas and a full dose of prescribed chemical fertilizers improved panicle length, biological yield, grain yield and thousand grains weight considerably more than others.